The vertical distribution of pollutants during export and long range transport: comparison of model simulations and A-train observations - Ford, Bonne Jane, author; Heald, Colette L., advisor; Kreidenweis, Sonia M., committee member; Peel, Jennifer L., committee member (Colorado State University. Libraries, 2011)
Due to increasing concern over the detrimental effects of pollution on visibility, human health, and agriculture, many countries have begun to set more stringent air quality regulations and to take measures to reduce local emissions. However, recent studies have also shown that long range transport (LRT) of pollution from upwind sources can make a non-negligible contribution to background concentrations and potentially inhibit a region's ability to meet air quality standards. Quantifying this contribution has become an important research initiative; however, a major hindrance in determining the impact of transported plumes on a receptor site lies in a lack of information on the vertical distribution of pollutants during export and transport from a source region. The vertical distribution can determine the efficiency of transport by way of dominant removal processes and wind strength, which will determine the final surface impact at a downwind site. In this study, we integrate aerosol extinction and optical depth observations from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP), aerosol optical depth AOD from the Moderate-resolution Imaging Spectroradiometer (MODIS) along with measurements of carbon monoxide (CO) from the Tropospheric Emission Spectrometer (TES) with simulations of species concentrations from a global chemical transport model (GEOS-Chem) to examine the differences in gas and aerosol phase transport in the Northern Hemisphere. The different vertical structures exhibited by gaseous and particulate phase pollution due to differing sources and sinks provide opportunities to evaluate the model representation of mechanisms that determine the vertical structure, and ultimately the impact of LRT downwind. While CALIOP has unprecedented vertical resolution, it, like TES, has a small footprint and wide distance between scans, with no cross-track scanning. Therefore, comparisons with these satellite observations are particularly susceptible to model transport errors, especially on short time scales. We choose to minimize the effect of these sampling biases by examining LRT on a seasonal timescale. From seasonal comparisons, it is evident that pollutants are exported from their source regions throughout the year; however, the most efficient transport of CO and aerosols happens in spring due to more efficient mechanisms for lofting. We also investigate the strong regional dependence, where pollutants experience higher lofting over the eastern coastal regions of Asia and North America compared to Europe. In GEOS-Chem, pollutants that are lofted are more efficiently transported, while pollutants in the boundary layer are quickly removed. For CO, GEOS-Chem shows no particular bias compared to observations in the vertical distribution; however, these CO observations have limited vertical sensitivity. Aerosol extinction observations from CALIOP have increased vertical sensitivity and suggest that GEOS-Chem shows a high bias in source regions such as East Asia and over Europe, and a conversely low bias in outflow regions.